The roles of sulfuric acid in new particle formation and growth in the mega-city of Beijing - Yue, D. L.; Hu, M.; Zhang, R. Y.; Wang, Z. B.; Zheng, J.; ZJ Wu; Wiedensohler, A.; He, L. Y.; Huang, X. F.; T. Zhu (Atmospheric Chemistry and Physics, 2010)
Simultaneous measurements of gaseous sulfuric acid and particle number size distributions were performed to investigate aerosol nucleation and growth during CAREBeijing-2008. The analysis of the measured aerosols and sulfuric acid with an aerosol dynamic model shows the dominant role of sulfuric acid in new particle formation (NPF) process but also in the subsequent growth in Beijing. Based on the data of twelve NPF events, the average formation rates (2-13 cm(-3) s(-1)) show a linear correlation with the sulfuric acid concentrations (R-2=0.85). Coagulation seems to play a significant role in reducing the number concentration of nucleation mode particles with the ratio of the coagulation loss to formation rate being 0.41 +/- 0.16. The apparent growth rates vary from 3 to 11 nm h(-1). Condensation of sulfuric acid and its subsequent neutralization by ammonia and coagulation contribute to the apparent particle growth on average 45 +/- 18% and 34 +/- 17%, respectively. The 30% higher concentration of sulfate than organic compounds in particles during the seven sulfur-rich NPF events but 20% lower concentration of sulfate during the five sulfur-poor type suggest that organic compounds are an important contributor to the growth of the freshly nucleated particles, especially during the sulfur-poor cases.
Keywords: aerosol formation; atmospheric nanoparticles; China; h2so4; Meteorology & Atmospheric Sciences; rates; site; size distribution